PENINGKATAN HASIL BELAJAR MATA PELAJARAN IPAS MENGGUNAKAN GAME LEARNINGAPPS PADA PESERTA DIDIK KELAS IV.A SD NEGERI 55 PALEMBANG - Khofifatun Nafiah; Somakim; Putri Mindarti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The learning outcomes of class IV.A students at SD Negeri 55 Palembang in science subjects are still low. When learning takes place, students have difficulty understanding science material, students consider science subjects boring, they are not liked by students and students lack enthusiasm in the learning process in science subjects, thus causing low student learning outcomes. Therefore, it requires innovation in learning by using learningapps games. This research aims to improve student learning outcomes in science and science subjects in class IV.A of SD Negeri 55 Palembang by using learningapps games. This research is Classroom Action Research (PTK) which consists of three cycles. Each cycle consists of four stages which include planning, implementing actions, observing and reflecting. The subjects of this research were class IV.A students, totaling 28 students consisting of 12 men and 16 women. Data collection techniques are carried out through tests (formative tests) and non-tests (observation, interviews and documentation). The results of the pre-cycle research showed that the average score was 61.43 with a percentage of 39.29%. In cycle I, the average score increased to 70 with a percentage of 53.57%. In cycle II, the average score increased to 78.57 and the percentage of completion became 75%. And in cycle III the average score increased to 89.29 with a percentage of 92.86%. It can be concluded that science subjects using learningapps games can improve student learning outcomes in class VI.A of SD Negeri 55 Palembang.